2017
DOI: 10.1363/psrh.12046
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Choice and Use of Dual Protection Among Women Living with HIV in Canada: Priorities for Integrated Care

Abstract: Future research should explore how sustained ART and broader contraceptive options can support women's sexual and reproductive health care needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Women in these relationships may not feel empowered to decide whether and when to have children. Low uptake of long-acting and preferred contraceptive methods among women living with HIV [ 19 ] may also explain the weak association between pregnancy intentions and outcomes. Unintended pregnancies are associated with an increased likelihood of negative feelings and experiences during pregnancy and in the postpartum period [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women in these relationships may not feel empowered to decide whether and when to have children. Low uptake of long-acting and preferred contraceptive methods among women living with HIV [ 19 ] may also explain the weak association between pregnancy intentions and outcomes. Unintended pregnancies are associated with an increased likelihood of negative feelings and experiences during pregnancy and in the postpartum period [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among women living with HIV of reproductive age in Canada, 60% have never discussed their reproductive goals with a healthcare provider since being diagnosed with HIV [ 17 ]. Additionally, uptake of effective contraceptive methods among women living with HIV who report wanting to avoid pregnancy is low [ 18 ], and the range of contraceptive methods used is more narrow compared to HIV negative women [ 19 ], underscoring the need and opportunity to better understand and address the sexual and reproductive health needs of women living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Also, we excluded women who were using hormonal contraception or IUD, which may exclude participants who used these products for regulation of abnormal menstruation. In our analysis of contraceptive use among women living with HIV in the CHIWOS study [29], we asked women who reported using the oral contraceptive pill, injectable hormonal contraception, and the contraceptive implant the reasons for using these methods. Women could report more than one reason.…”
Section: Discussionmentioning
confidence: 99%
“…19 Less than 20% of women living with HIV in Canada practise WHO-defined dual protection, and 40% practised an expanded definition of dual protection (long-acting, reversible contraception plus either condoms or a suppressed HIV viral load). 17 The range of contraceptive methods used by women living with HIV is also more limited compared to women in the general Canadian population. 17 Among women living with HIV, studies suggest that awareness about safer conception methods 20 , 21 and the prevalence of receiving pre-conception counselling are low.…”
Section: Introductionmentioning
confidence: 99%
“… 17 The range of contraceptive methods used by women living with HIV is also more limited compared to women in the general Canadian population. 17 Among women living with HIV, studies suggest that awareness about safer conception methods 20 , 21 and the prevalence of receiving pre-conception counselling are low. 21 …”
Section: Introductionmentioning
confidence: 99%